Six‐Minute Walk Test Is Superior to Grip Strength as a Marker of Functional Recovery During Cancer Cachexia Rehabilitation - Addison Barber; Amber Willbanks; Kathryn Abplanalp; Christopher W. Lewis; Ben Binder‐Markey; Prakash Jayabalan; Richard L. Lieber; Ishan Roy (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Decline in functional independence is a defining event of cancer cachexia, and attempts at creating cachexia‐specific therapies have largely failed because of the inability to identify treatments that improve functional capacity. This may be, in part, due to a lack of outcomes that are appropriate and sensitive enough to detect functional recovery. Grip strength is a frequently used outcome measure in cachexia clinical studies; however, the use of gait‐based measures is now emerging. These two outcome measures have never been directly compared in the same cohort of cachexia patients regarding their ability to measure and relationship to functional independence. We hypothesize that gait‐based measures more comprehensively act as a proxy measure for functional independence related to cachexia. Methods In a retrospective cohort study of 485 cancer patients with a range of cachexia severity and related functional decline who required care at a single‐centre inpatient rehabilitation facility (IRF), we assessed the six‐minute walk test (6MWT) and hand grip strength (hGS) as proxy measures for functional capacity. Functional capacity is defined as mobility and activities of daily living (ADLs), is quantified by measures of functional independence and referred to here as the Total Motor Score. Cachexia patients were identified primarily using the Fearon et al. consensus criteria, with secondary identification by the Weight Loss Grading Scale (WLGS), Prognostic Nutritional Index (PNI) and neutrophil‐to‐lymphocyte ratio (NLR). Primary outcomes were change/gain in Total Motor Score, IRF discharge destination (e.g., homebound status or need for care facility) and 6‐month survival. Results The presence of cachexia in this cohort was 63%. This cohort was 52% male. Mean age was 63 ± 0.63 (SEM) years. Multivariate linear regression demonstrated that change in 6MWT (p < 0.0001) but not hGS (p = 0.084) correlated with Total Motor Score gain after controlling for age, disease burden, cancer type, previous cancer treatment and baseline motor function as covariates. Area under the curve analysis revealed that change in 6MWT (p < 0.0001, AUC = 0.77) was a stronger predictor of Total Motor Score gain than hGS (p = 0.0016, AUC = 0.59). In a multivariate logistic regression model, discharge from IRF to home with independence was predicted by change in 6MWT (p = 0.0007) but not hGS (p = 0.8075). Six‐month survival post‐rehabilitation was predicted by change in 6MWT (p = 0.0345) but not hGS (p = 0.9025) in a multivariate Cox proportional hazards model. Conclusions Multiple analytical approaches to our data set demonstrate that changes in 6MWT are better associated with cachexia‐related outcomes and should be included in future cachexia studies.